ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN FVA (FINANCIAL VALUE ADDED) PADA PERBANKAN SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2024 - Kholifah, Siti; Nusantoro, Jawoto; Darmayanti, Elmira Febri (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to analyze the financial performance of Sharia banking institutions listed on the Indonesia Stock Exchange based on liquidity, solvency, profitability, and Financial Value Added (FVA). This research employs a descriptive quantitative approach. The data used are secondary data collected through documentation techniques. The secondary data were obtained from the financial reports of Sharia banks listed on the IDX, accessed via the official IDX website at www.idx.co.id. This study uses purposive sampling with specific criteria, resulting in four Sharia banks selected as samples. The results show that the financial performance analysis of Sharia banks listed on the Indonesia Stock Exchange based on liquidity varies during the 2021–2024 period. Based on solvency, the financial performance of the four sampled Sharia banks is categorized as very healthy. Profitability analysis shows varied results. Meanwhile, based on FVA, Bank Syariah Indonesia and Bank BTPN Syariah show positive FVA values throughout the study period, indicating good financial performance.